Simultaneous photoelectrocatalytic hydrogen production and ammonia degradation using titania nanotube-based photoanodes - Elysabeth, Tiur; Dewi, Eniya Listiani; Ratnawati; Mulia, Kamarza; Slamet (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
The primary focus of this research is to enhance the efficiency and effectiveness of the photoanode based of titania nanotubes in the photoelectrocatalytic process, which enables the simultaneous generation of hydrogen and degradation of ammonia. The modification process involved the incorporation of nitrogen dopant during anodization and sensitization of CuO through Successive Ionic Layer Adsorption Reaction (SILAR). The results of this study showed that the introduction of N dopant led to a significant enhancement in both the ammonia elimination and the hydrogen production, as evidenced by 3N-TiNTAs achieving 74.4% and 561 mmol/m2, respectively. Meanwhile, the highest hydrogen production was observed with 7CuO-TiNTAs at 910.14 mmol/m2. The study revealed that N-TiNTAs exhibited superior performance in ammonia degradation; while CuO-TiNTAs showed higher hydrogen production rates. Furthermore, the mechanistic aspects of the study were also thoroughly examined.